Ancient names origins. Water roots and place-names in the prehistoric ligurian context - Perono Cacciafoco, Francesco (2015)
Ancient Names Origins. Water Roots and Place-Names in the Prehistoric Ligurian Context. This paper outlines a new applied epistemological aspect of the so-called Convergence Theory, that is aimed at develop a potentially 'homogeneous' vision between the different approaches in the field of the Indo-European Linguistics. This work tries to 'reconstruct' a sort of Italian and European 'macro-area' (or 'micro-area') characterized by places names linked to the word-root *alb-, with a delineation of the 'semantic steps' produced, over the centuries, by the same word-root, following a potential all-embracing approach. It seems that Paleo-Ligurian place names of the type Alba, Old European river names Albis and the like, as well as their ablauting forms Olb- (> Orb- in Romance Ligurian), do not reflect directly the proto-Indo-European adjective *albho-, 'white'; rather, they all seem to continue a pre-proto-Indo-European extended root *Hal-bh-, 'water', cognate with the Sumerian ḫalbia (> Akkadian ḫalpium, 'spring', 'well', 'water mass', 'water hole'). A further analysis of the same *Hal-bh-, moreover, leads to a comparison with the proto-Indo-European root *Hal-, 'nourish'. The proto-Indo-European suffixed form *HwaH-r-, 'water', then, exhibits a similar diffusion.